Regarding the sunshield at the top of ST1-ST5, ST11-ST13 and ST16-ST17 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the sunshield at the top of ST1-ST5, ST11-ST13 and ST16-ST17 of BRACU new campus building.